Market price stabilizing strategy: overview of the combination of SWOT and QSPM analysis - Sarkum, Sumitro; Watrianthos, Ronal (JURNAL MANAJEMEN MOTIVASI, 2018)
The purpose of this study was to solve the problem of brick price instability in the market and to add new income to brick artisans. This effort made to improving their welfare. The solution from previous research suggests that it form a cooperative as a business unit to stabilize prices in the market. While the results of field observations and interviews conducted with brick artisans found that prices that were always unstable became the main problem. While the cooperative paradigm that formed in the perspective of society is still seen as a microfinance institution that is only used to borrow money when the economic situation of the craftsmen decreases. Based on previous research and problems that occur, a problem-solving solution is needed. Both of these reasons form the basis of this research to find out what to do and what strategies should be prioritized and what policies must be taken by brick makers.